Preserving local identity in digital age: A study on local identity in digital spaces of East Nusa Tenggara teenagers - Maxymilianus Soter Mite Kombong; Mentari Putri Pramanenda Sinaga; Arnoldus Freinademetz Teda (Linguistics Initiative, 2026)
This research is qualitative research on local identity of the East Nusa Tenggara Teenagers in digital spaces. It aims to examine how East Nusa Tenggara Teenagers preserve their local identity in digital platforms. Cultural Identity Theory (CIT) is used to explore how participants shape their identity in digital communication. There are ten teenagers participated in this research. In-depth interview was conducted to get a deep understanding. The research finds that East Nusa Tenggara Teenagers have a good linguistics awareness when interact to others through digital platforms. A positive attitude by the East Nusa Tenggara Teenagers toward local culture in digital spaces is also occurred in this research. Local values and norms are also can be integrated through digital spaces. The result of this research suggests implication for future research of how local culture and digital spaces can integrate each other.